Evaluation of aspartate aminotransferase to platelet ratio index and fibrosis 4 scores for hepatic fibrosis assessment compared with transient elastography in chronic hepatitis C patients - Pimsiri Sripongpun (2020)
© 2019 The Authors. JGH Open: An open access journal of gastroenterology and hepatology published by Journal of Gastroenterology and Hepatology Foundation and John Wiley & Sons Australia, Ltd. Background and Aim: Fibrotic stage (FS) assessment is essential in chronic hepatitis C treatment cascade. Liver stiffness measurement (LSM) using transient elastography (TE) is reliable and correlated with liver biopsy. However, TE may not be widely available. This study aimed to evaluate the diagnostic performances of aspartate aminotransferase to platelet ratio index (APRI) and fibrosis 4 (FIB-4) scores compared with TE. Methods: We conducted a multicenter, cross-sectional study, including all chronic hepatitis C virus (HCV) monoinfection patients with successful and reliable LSM, at 10 centers in Thailand from 2012 to 2017. Characteristics and laboratory data within 3 months of TE were retrospectively reviewed. Using TE as a reference standard, the diagnostic performances of APRI and FIB-4 were evaluated. TE cut-off levels of 7.1 and 12.5 kPa represented significant fibrosis (SF) and cirrhosis, respectively. Results: The distribution of FS by TE in 2000 eligible patients was as follows: no SF 28.3%, SF 31.4%, and cirrhosis 40.3%. APRI ≥ 1 provided 70.1% sensitivity and 80.6% specificity, with an area under the receiver operator characteristics curve (AUROC) of 0.834 for cirrhosis. The specificity increased to 96.3% when using a cut-off level of APRI ≥ 2. FIB-4 ≥ 1.45 provided a sensitivity, specificity, and AUROC of 52.4%, 91.0%, and 0.829 for cirrhosis, respectively. For SF, APRI performed better than FIB-4, with an AUROC of 0.84 versus 0.80 (P < 0.001). APRI score < 0.5 and FIB-4 score > 1.45 yielded sensitivities of 82.3% and 74.4% and specificities of 65.4% and 69.8%, respectively. Conclusions: APRI and FIB-4 scores had good diagnostic performances for FS assessment compared with TE, especially for cirrhosis. APRI may be used as the noninvasive assessment in resource-limited settings for HCV patients’ management.